(untitled) (مجلة التربوي, 2025)
This study aimed to a comprehensive overview of fish muscle physiology, emphasizing its critical role in aquaculture practices and research and explore the intricate mechanisms underlying muscle development, including myogenesis, muscle fiber types, and their physiological properties. The study also overview the importance of understanding muscle fiber hyperplasia and hypertrophy, as well as the structural characteristics of fish musculature, to optimize breeding programs and management strategies in aquaculture. Additionally, the study delves into the impact of environmental factors, such as temperature and water quality, on muscle development. A comprehensive literature search was conducted using databases Google Scholar, and Web of Science to gather relevant studies on fish muscle physiology, myogenesis, muscle fiber types, hyperplasia and hypertrophy, and the impact of environmental factors on muscle development. Inclusion criteria included studies conducted on various fish species. Exclusion criteria included studies on non-fish species, and studies not available in full text. The results of this study declear that the integration of advanced omics technologies-genomics, transcriptomics, proteomics, and metabolomics is proposed means to uncover molecular signatures and regulatory networks governing muscle physiology. The study also emphasizes the need for sustainable aquaculture practices that align with global goals for environmental stewardship and economic viability. Ultimately, this work seeks to contribute to the development of effective strategies for enhancing fish muscle quality and ensuring the sustainability of aquaculture systems, benefiting both human populations and marine ecosystems.